2014
DOI: 10.1371/journal.pone.0103348
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Laser Irradiation Improves Functional Recovery and Nerve Regeneration in Sciatic Nerve Crush Rat Injury Model

Abstract: The development of noninvasive approaches to facilitate the regeneration of post-traumatic nerve injury is important for clinical rehabilitation. In this study, we investigated the effective dose of noninvasive 808-nm low-level laser therapy (LLLT) on sciatic nerve crush rat injury model. Thirty-six male Sprague Dawley rats were divided into 6 experimental groups: a normal group with or without 808-nm LLLT at 8 J/cm2 and a sciatic nerve crush injury group with or without 808-nm LLLT at 3, 8 or 15 J/cm2. Rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 45 publications
1
51
0
2
Order By: Relevance
“…Regarding the use of LLLT, the most effective laser application with regard to wavelength, energy density, exposure time, and pulsed or continuous wave is still controversial, but its use is suggested to facilitate the nerve regeneration [27,43]. Based in this study, on the statistical data, similar results were observed in most measured variables, when comparing EGS to EGSL and EGF to EGFL in both periods, but with mean values almost always favorable with laser therapy.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Regarding the use of LLLT, the most effective laser application with regard to wavelength, energy density, exposure time, and pulsed or continuous wave is still controversial, but its use is suggested to facilitate the nerve regeneration [27,43]. Based in this study, on the statistical data, similar results were observed in most measured variables, when comparing EGS to EGSL and EGF to EGFL in both periods, but with mean values almost always favorable with laser therapy.…”
Section: Discussionsupporting
confidence: 65%
“…The laser source had been previously tested to certify the dose. The laser therapy applications were performed 1 day after surgery, and in the postoperative period, three times a week for a total of 5 weeks [27][28][29].…”
Section: Laser Irradiationmentioning
confidence: 99%
“…Among the effects of PBMT on nerve injury, it was verified that the laser minimized the side effects of bupivacaine on the nerve and on the muscle [29], potentiated the process of nerve regeneration observed by morpho-quantitative analysis of the axons and of the nerve fibers [2,3,19,30,31,32,33,34,35], in addition to assisting muscular reinnervation [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Yet, high reproducibility of the lesion makes this experimental model also particularly suitable for investigating regeneration-related time course changes (De Leon et al, 1991;Gupta and Channual, 2006;Sta et al, 2014). Finally, changes in the outcome of nerve regeneration after a crush injury of the sciatic nerve might be used as a pre-clinical end-point predictor of the effectiveness of a therapeutic agent and/or tissue engineering strategy on nerve regeneration (Fleming et al, 2007;Amado et al, 2008;Baptista et al, 2008;Gigo-Benato et al, 2010;Dadon-Nachum et al, 2011;Kilic et al, 2013;Wang et al, 2014).…”
Section: Compression Lesionsmentioning
confidence: 99%